Additions to the microfungi in Taiwan: introducing Pseudorobillarda camelliae-sinensis sp. nov., (Pseudorobillardaceae) and new host records of pleosporalean taxa in mountainous habitats - Rathnayaka, Achala R.; Chethana, K.w. Thilini; Tennakoon, Danushka S.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2021)
A novel taxon, Pseudorobillarda camelliae-sinensis (Pseudorobillardaceae) and new host records of pleosporalean taxa viz. Neopyrenochaeta triseptatispora (Neopyrenochaetaceae), Ramusculicola thailandica (Teichosporaceae) and Vaginatispora palmae (Lophiostomataceae) resulted from our investigation of plant-associated microfungi in Alishan and Fenghuang Mountain ranges in Taiwan. These taxa were isolated from dicotyledonous hosts of Bignoniaceae, Caprifoliaceae, Meliaceae and Moraceae. Maximum likelihood and Bayesian inference analyses were performed using combined SSU, LSU, ITS, tef1-α and rpb2 sequence data to clarify the phylogenetic affinities of taxa. The newly described taxa of the current study are accompanied by comprehensive descriptions, micrographs and comparisons with similar species. In addition, the importance of exploiting fungi from mountain habitats in Taiwan is discussed.